(untitled) (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This study investigated the effect of salinity stress on the third leaf area and leaf number of red bean varieties and accessions. Our results showed that salinity negatively affected the bean plants, leading to a reduction in leaf number and a decrease in leaf area. This response can be explained by the toxic effects of salts under saline conditions, which limit nutrient uptake and disrupt normal growth.